Advertisement Remove all ads

Solve : 4x - 2 - 2x + 1 = 0 - Mathematics

Sum

Solve :  4x - 2 - 2x + 1 = 0

Advertisement Remove all ads

Solution

4x - 2 - 2x + 1 = 0
⇒ 4x - 2 = 2x + 1
⇒ (22)x - 2  = 2x + 1
⇒ 22x - 4  = 2x + 1
We know that if bases are equal, the powers are equal
⇒ 2x - 4 = x + 1
⇒ 2x - x = 4 + 1
⇒ x = 5.

Concept: Solving Exponential Equations
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 9 ICSE
Chapter 7 Indices (Exponents)
Exercise 7 (B) | Q 3.1 | Page 100
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×